Implementasi Metode Naive Bayes Pada Diagnosis Penyakit Lambung - Trio Pamujo Wicaksono; Nurul Hidayat; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Internal disease is a disease associated with many vital organs in the human body, one of which is the Stomach. Stomach is an important organ in the body because it is one of the digestive organs of food and beverages consumed by humans. Gastric disease is less known to the public due to lack of information and knowledge about gastric disease so that people ignore the symptoms that arise. Lack of gastric disease specialist doctors also become the trigger of obstacles in the role of prevention of stomach disease early on so that required a system that has the ability as an expert by providing a certainty value. Therefore, based on the needs of a physician and the general public in overcoming the shortage of doctors, it takes an expert system application that is capable of diagnosing gastric disease so that the community needs for handling the illness can be fulfilled, it can be built software engineering with Naive Bayes method to diagnose disease hull using android based applications.